Coordinates-based meta-analysis for vestibular migraine and the underlying mechanisms behind it - Fan, Xiaoping; Dong, Liang; Li, Hui; Wang, Kuiyun; Zhou, Jiying (Frontiers in Neurology, 2025)
BackgroundVestibular migraine (VM) is a leading cause of recurrent vertigo episodes. Voxel-based morphometry (VBM) is a reliable technique to analyze structural changes, particularly in gray matter (GM) volume, across various neurological conditions. Despite the growing amount of neuroimaging data in recent decades, a comprehensive review of GM alterations in VM remains lacking.MethodsWe conducted a systematic review of three English-language databases (PubMed, Embase, and Web of Science) and two Chinese-language databases (China National Knowledge Infrastructure and Wanfang) to evaluate existing neuroimaging data on GM volume in VM patients. A coordinate-based meta-analysis (CBMA) was performed using the latest algorithm, seed-based d mapping with permutation of subject images (SDM-PSI), to identify brain alterations across individual studies.ResultsFive studies (103 VM patients, 107 HCs) were included. The CBMA demonstrated a significant reduction in GM volume in VM patients compared to HCs, with peak convergence in the left rolandic operculum (SDM-Z = −3.68, p-corrected = 0.004, voxels = 629; Brodmann area 48), extending to the posterior insula. Heterogeneity across studies was low (I2 = 19.35%), and no publication bias was detected (Egger’s test: p = 0.826).ConclusionThis meta-analysis confirms reliable GM volume alterations in the posterior insula–operculum region of VM patients. Longitudinal studies with standardized imaging protocols are needed to clarify whether these changes are causes or consequences of VM.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021277684.